2012
DOI: 10.1186/1297-9716-43-66
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma haemocanis – the canine hemoplasma and its feline counterpart in the genomic era

Abstract: Mycoplasma haemocanis is a hemotrophic mycoplasma (hemoplasma), blood pathogen that may cause acute disease in immunosuppressed or splenectomized dogs. The genome of the strain Illinois, isolated from blood of a naturally infected dog, has been entirely sequenced and annotated to gain a better understanding of the biology of M. haemocanis. Its single circular chromosome has 919 992 bp and a low G + C content (35%), representing a typical mycoplasmal genome. A gene-by-gene comparison against its feline counterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…A similar result, in which Mhc and Mhf 16S rRNA gene sequences shared >99% identity, has been previously reported (Brinson and Messick, 2001). However, phylogenetic studies based on the RNase P RNA gene showed that Mhc is a distinct species infecting the dog (do Nascimento et al, 2012). Unfortunately further phylogenetic analysis was not possible in the current study as insufficient haemoplasma DNA was available from these dogs for further amplification studies.…”
Section: Discussionsupporting
confidence: 86%
“…A similar result, in which Mhc and Mhf 16S rRNA gene sequences shared >99% identity, has been previously reported (Brinson and Messick, 2001). However, phylogenetic studies based on the RNase P RNA gene showed that Mhc is a distinct species infecting the dog (do Nascimento et al, 2012). Unfortunately further phylogenetic analysis was not possible in the current study as insufficient haemoplasma DNA was available from these dogs for further amplification studies.…”
Section: Discussionsupporting
confidence: 86%
“…M. parvum has the smallest single, circular chromosome of all the Mycoplasma genomes sequenced to date. The characteristics of the M. parvum genome, including its small size, low G + C content, use of UGA codon to encode tryptophan, and number of tRNA and rRNA were in agreement with those reported for the genomes of other hemoplasmas and are typical of mycoplasmas [ 1 , 4 , 6 ]. In addition, the percentage of CDS dedicated to paralogous genes (24.3%) was similar to that reported for other hemoplasmas [ 1 8 , 10 ].…”
Section: Discussionsupporting
confidence: 85%
“…Earlier studies have reported trinucleotide motif GAA(n) in pMGA of M. gallisepticum 17,50,51 The most abundant repeat motif is AAT followed by TAA but CG rich trinucleotide repeats are present in few Mycoplasmas (data not shown). Earlier study reports GAT repeats in rpoD gene, ATT repeat in pgsA gene, GAA in oppA gene of M. hominis 53 54 . The present study shows TTC repeats in two hypothetical protein CDS (data not shown) and one in Transport (permease) CDS (data not shown).…”
Section: Abundance Of Trinucleotide Repeatsmentioning
confidence: 85%